Preparation and property characterization of chitosan/polyvinyl alcohol filtration film - ZHAO Xiao-yan; HUANG Chen; ZHANG Shuai; WANG Chen-yi (Cailiao gongcheng, 2020)
CS (chitosan)/PVA (polyvinyl alcohol) film was prepared by scraping, and then soaking it in a coagulation bath. The morphology and structure of CS/PVA films at different solidification time were investigated. Bovine serum albumin (BSA) and three different disperse dyes (disperse yellow, disperse black and disperse blue) were used as targets to investigate the filtration and adsorption performance of the CS/PVA film. The results show that the CS/PVA film can obtain a relatively complete surface structure and porous internal structure after soaking in coagulation bath for 40 min during the phase separation of film. The pure water flux of CS/PVA composite film is (90.56±3.92) L/(m2·h) and the rejection of CS/PVA composite film for BSA is (93.33±2.83)%. The filtration and adsorption properties of CS/PVA composite film for disperse yellow, disperse black and disperse blue dyes were further investigated. The good filtration and adsorption capacity for disperse dyes is due to the complete and compact surface structure of CS/PVA composite film which provide an effective physical barrier to dyes. In addition, the hydroxyl group in the molecular structure of the composite membrane can interact with the amino group of the target dye to form intramolecular hydrogen bonds, which further improve the dye adsorption capacity of the filter membrane. At 130 min, the filtration and adsorption of disperse yellow, disperse black and disperse blue dyes tend to be balanced gradually(The initial concentration of dyes is 0.1 g/L and the operating pressure of filtration is 0.15 MPa), and the filtration and adsorption equilibrium are (294.42±1.34),(257.77±0.28), (210.74±1.06) mg/g, respectively. The dye removal rate of CS/PVA composite film can reach above 96% in NaOH solution, which is conducive to the reuse of the film.